(untitled) (Sahel Journal of Life Sciences FUDMA, 2024)
Parasites are ubiquitous and fish are host to some of these parasites that can be zoonotic. Assessing their status and trends is vital in public health safety, and aquatic ecology. The study aimed to identify parasites, assess the prevalence, identify the infection sites and also determine the variation in infection among sexes in fish from River Orogodo, Agbor, Delta State. A total of 780 fish, comprising 23 species belonging to 12 fish families were collected between September 2014 and August 2019 using cast nets of various mesh sizes and funnel entrance traps. Fishes were identified and examined using standard morphological keys.Â According to established procedures, parasitological indexes were determined by inspecting various external and internal body parts. The overall prevalence recovered was 196 (25.1%) with twenty-two parasites including larvae stages both from external and internal parts of the fish. These include 5 protozoans (Microsporidium gen sp, Trichodina spp, Epistylis sp, Crytobia sp and Chilodonella sp), Myxobolus sp, 5 nematodes (Procamallanus laevionchus, Camallanus sp, Cucullanus sp, contracaecum larvae, Rhabdochona sp); 3 acanthocephalans (Acanthogyrus sp, Neoerchinorhynchus sp and Acanthocephalus sp), 4 cestodes (Monobothroides woodlandi, Wenyonia sp, Proteocephalid sp including plerocercoid larvae); 3 digeneans (Clinostomum sp, Euclinostomum heterostomum, Centrocestus sp, unidentified metacerceriae in the liver). The study revealed that female fish (32.5%) were more infected than their male counterparts (26.4%). The results indicate that fishes in River Orogodo, Delta State are hosts of various external and internal parasites, which may be of public health and aquacultural importance.